2021
DOI: 10.25248/reas.e9036.2021
|View full text |Cite
|
Sign up to set email alerts
|

Transtorno do espectro autista: o impacto na dinâmica familiar e as habilidades no cuidado

Abstract: Objetivo: Entender o Transtorno do Espectro Autista (TEA) no que tange as suas características comportamentais, o impacto disso na dinâmica familiar, além de identificar algumas habilidades no cuidado. Revisão bibliográfica: As manifestações comportamentais do TEA se apresentam precocemente. Dentre eles, tem-se irregularidade e atraso no controle e desenvolvimento motor; dificuldade para reconhecer emoções, apresentando um afeto negativo; sensibilidade diminuída a recompensas sociais; e dificuldade para manter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…It was observed that the majority of the sample was made up of male children, a result similar to those found in studies carried out by De Paula et al [22] and Marques et al [23], who verified the prevalence of males in the diagnosis of ASD. The results corroborate the ratio between the male and female sexes of 4:1, according to DSM-5 [6], and the ratio of 3:1, according to the meta-analysis carried out by Loomes et al [24].…”
Section: Discussionsupporting
confidence: 86%
“…It was observed that the majority of the sample was made up of male children, a result similar to those found in studies carried out by De Paula et al [22] and Marques et al [23], who verified the prevalence of males in the diagnosis of ASD. The results corroborate the ratio between the male and female sexes of 4:1, according to DSM-5 [6], and the ratio of 3:1, according to the meta-analysis carried out by Loomes et al [24].…”
Section: Discussionsupporting
confidence: 86%